Estrategias de marketing y su incidencia en el comportamiento del consumidor en la empresa casa ferretería Fong S.A. Ferrefong, año 2023 - García Jaramillo, Noelia Kiabeth (2025)
This research project analyzes the impact of marketing strategies on consumer behavior, given the challenges Casa Ferretería Fong S.A. faces in maintaining its competitiveness, attracting new customers, and fostering loyalty. A mixed-methodological approach was used, combining qualitative and quantitative factors, with a representative sample of 383 current customers. A structured questionnaire was used to evaluate the main research variables: communication channels, marketing strategies, consumer behavior, and customer satisfaction. An interview was also conducted to understand the marketing strategies implemented by the hardware store. The data obtained from the survey were analyzed using SPSS V26 software